Correlates of Positivity Among a Sample of Lebanese University Students - Moussa, Sara; Malaeb, Diana; Obeid, Sahar; Hallit, Souheil (Frontiers in Psychology, 2022)
Background: People say it is hard to stay truly positive in Lebanon. Studies showed that 63% of Lebanese young adults are highly dissatisfied with their country. In fact, young adults are the most vulnerable population to stressors in Lebanon since their future is at stake and it is their time to shape their lives in a country that cripples them. This study aimed to assess factors (flourishing, religious coping, experiences in life and the economic burden) associated with positivity among a sample of Lebanese university students despite the various stressors they are facing on top of the economic collapse and the COVID-19 pandemic. Methods: This cross-sectional study was conducted between November and December 2021. A total of 333 participants (219 females, 114 males; mean age = 22.95 ± 4.79 years) was recruited through convenience sampling and snowball technique through several areas in Lebanon’s governorates. A linear regression taking the positivity score as the dependent variable was adopted and all variables that showed a correlation > │0.24│ in absolute value were entered in the final model as independent. Results: A linear regression taking the positivity score as the dependent variable, showed that more positive experiences in life (Beta=0.49; 95% CI 0.35-0.62), more flourishing (Beta=0.10; 95% CI 0.05-0.14), living in rural area compared to urban (Beta=3.06; 95% CI 2.02-4.11) and female gender (Beta=1.56; 95% CI 0.50-2.61) were significantly associated with more positivity (Nagelkerke R2 of the model= 45.8%). Conclusion: This study demonstrated that the youth’s positivity is strongly affected by age, gender, residency, and the country they live in that will both directly and indirectly shape their life experiences and their ability to flourish and prosper. Along with all the efforts done to help during this collapse and alleviate the stress that young adults are enduring, follow-up studies are still needed to determine accurate coping techniques that pushes these young adults to think positively in a country where negativity reigns and all else fails.